PENGARUH EMBARGO SENJATA AS TERHADAP KERJASAMA TEKNIK MILITER RI-RUSIA TAHUN 2003 - Nurak, Anastacia Patricia Novlina; Dharmiasih, D.A. Wiwik; Nugraha, A.A Bgs Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACT This research described the influence of arms embargoes from U.S for Indonesia’s military in 1999 that implied the military technical cooperation between Indonesia and Rusia in 2003. This research is using qualitative method with literature review and secondary data. This research using security dilemma concept for observed the increase of military capability from countries around Indonesia when Indonesia’s military capability has decrease because of U.S embargo, and then using defensive realism theory for apprehend Indonesia’s action to build military technical cooperation with Rusia. The result from this research showed that U.S arms embargo causes the reduction of Indonesia’s military power and security dilemma in Indonesia. The conclusion from this research is U.S arms embargo influenced Indonesia’s action for build on military cooperation with Rusia, which is the behavior from defensive realism. Keyword : Influence, U.S Arms Embargo, Military Technical Cooperation between RI-Rusia 2003, Security Dilemma